To find the distance between points E and F using the distance formula, we first recall the points: \(E(-6, 1)\) and \(F(2, -5)\).
The distance formula between two points \((x_1, y_1)\) and \((x_2, y_2)\) is given by:
\[ d = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \]
With \(E\) as \((x_1, y_1)\) = \((-6, 1)\) and \(F\) as \((x_2, y_2)\) = \((2, -5)\), we substitute these values into the formula:
\[ d = \sqrt{(2 - (-6))^2 + (-5 - 1)^2} \] which simplifies to: \[ d = \sqrt{(2 + 6)^2 + (-5 - 1)^2} \] or: \[ d = \sqrt{(8)^2 + (-6)^2} \]
Now, let's look at the responses provided. The correct setup using the distance formula is:
\[ d = \sqrt{(2 - (-6))^2 + (-5 - 1)^2} \]
So the correct choice among the options is:
d = \sqrt{(−6−2)^2 + (1−(−5))^2} (This is incorrectly expressed, but if intended to show the operation for finding distance could resemble a similar structure; however, the accurate representation is given above).
Therefore, the closest correct answer, representing the step of finding distance in appropriate terms, is:
Final correct setup: \[ d = \sqrt{(2 + 6)^2 + (-5 - 1)^2} \]
However, in the options given, ensure to select the setup best representing the calculation.